Eco-efficiency assessment of pork production through life-cycle assessment and product system value in South Africa - Qalase, C.; Harding, K.G. (EDP Sciences, 2022)
The consumption of pork as a source of animal protein has increased worldwide, especially in developing countries such as South Africa. The increase in pork demand is putting pressure on the natural environment, and the costs of production are increasing. This study sought to determine what is the eco-efficiency of pork production in a South African context. It also was meant to determine which processes in the value chain have low eco-efficiencies. Lastly, it sought to find what strategies could be recommended to improve overall eco-efficiency. Eco-efficiency was assessed by following the requirements of the International Standards Organisation ISO 14045 standard, which requires that the Life cycle assessment (LCA) method and product system value be combined. The environmental life cycle costing (LCC) method was used to determine the product system value (Value Added) of pork production. The functional unit was 1 kg of pork carcass, specifically from the cradle to the abattoir gate. The findings indicated that the pig farm and abattoir were the processes that had low eco-efficiencies and eco-efficient strategic improvements could be made. Mitigation strategies could be developed to concentrate on the production of animal feed and the use of renewable energy sources at the abattoir. The use of water could be improved by automation of the abattoir processes. Therefore, this study achieved its goal as economic and environmental areas of interest were identified in this specific case study for South Africa. This framework could be extended to study the eco-efficiency of other meat production chains and other sectors.
Conference Paper
Keywords: Eco-efficiency; Pork Production; Pig Farm; Abbattoir